Effect of exhaustive exercise on human neutrophils in athletes - Yamada, M.; Suzuki, K.; Kudo, S.; Totsuka, M.; Simoyama, T.; Nakaji, S.; Sugawara, K. (Luminescence, 2000)
In order to investigate the effect of exercise on the capacity of neutrophils to produce reactive oxygen species (ROS), eight male cross-country skiers underwent maximal exercise. Peripheral blood samples were taken pre-exercise, 0 h, 1 h, and 2 h after finishing maximal exercise. Leukocyte counts significantly increased (p < 0. 05), particularly lymphocytes (p < 0.05), just after the exercise period (0 h) and significantly increased again (p < 0.05), particularly neutrophils (p < 0.05), 2 h after the exercise compared with pre-exercise values. The capacity of isolated neutrophils to produce ROS was assessed by lucigenin (Lg)-dependent chemiluminescence (CL) and luminol (Lm)-dependent CL on stimulation with opsonized zymosan (OZ) and phorbol myristate acetate (PMA). Just after exercise, the LgCL response was not affected, while the response of LmCL mixed with sodium azide, which inhibits catalase and myeloperoxidase (MPO) activity, was significantly enhanced (p < 0.05). In addition, just after exercise, the level of serum growth hormone increased significantly (p < 0.05). The serum cortisol level also increased significantly just after and 1 h after exercise (p < 0.05). These data indicated that maximal exercise not only mobilized neutrophils from marginated pools into the circulation, but also caused increased ROS generation. Copyright 2000 John Wiley & Sons, Ltd.